2020
DOI: 10.1371/journal.pone.0244014
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with divorce from first union among women in Ethiopia: Further analysis of the 2016 Ethiopia demographic and health survey data

Abstract: Background Globally, divorce is a common phenomenon in couples' marital life. As a result, many divorced couples and their children face several social, economic, and health problems after dissolution. There is little information on the magnitude and determinants of divorce in developing countries including Ethiopia. Therefore, this study aimed to estimate the prevalence of divorce from the first union and its predictors among reproductive-age women in Ethiopia. Methods We used the 2016 Ethiopia demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 39 publications
7
17
0
Order By: Relevance
“…This study aimed to investigate the prevalence of marriage dissolution among married people in Hosanna Township. The prevalence of marital dissolution in this study area was 26.0%, which was comparable to that of study in Ethiopia, where approximately 25% of married women were reported to be divorced from their first relationship [ 18 ].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This study aimed to investigate the prevalence of marriage dissolution among married people in Hosanna Township. The prevalence of marital dissolution in this study area was 26.0%, which was comparable to that of study in Ethiopia, where approximately 25% of married women were reported to be divorced from their first relationship [ 18 ].…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, another study in rural South Africa indirectly revealed the effect of education on marriage dissolution and reported that those with higher education were more likely to remain in one marriage than those who had never attended school [ 19 ]. Being limited to women and methodological differences between the previous and the current study could more likely explain the observed differences [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of eight covariates were controlled for in the present study. The variables were selected based on their availability in the DHS dataset as well as their significant association with divorce or separation ( Dagnew et al, 2020 ; Wagman et al, 2016 ). In the analysis, we utilised the existing coding in the DHS dataset for maternal age (years), educational level, current working status.…”
Section: Study Variablesmentioning
confidence: 99%
“…This study has some limitations. Many factors other than the ages at first marriage influence the likelihood of marital dissolution [14,46,47], but we do not have the necessary data for adjusting our models for all those variables. One such variable is the duration of a marital relationship, which is a potential risk factor for marital stability [20].…”
Section: Discussionmentioning
confidence: 99%